Effect of dried orange peel on egg production and quality of laying hen - Ahmed, ST; Hasan, MM; Resmi, SI; Islam, MW; Rahman , M (Bangladesh Journal of Animal Science, 2022)
Utilization of agricultural by-products in animal nutrition is a practice as old as the domestication of animals. The dried orange peel (DOP), by-product of citrus industry is a promising source of diversified bioactive ingredients with beneficial effects on health. Therefore, this study was carried out to assess the dietary effect of DOP on production and, internal and external egg quality characteristics of laying hens. A total of 60 layers of 25 weeks of age were segregated into three dietary treatment groups using a completely randomized design and reared up to 42 weeks. The dietary treatments were control (basal diet), 5% DOP (basal diet + 5% DOP), and 10% DOP (basal diet + 10% DOP). The study revealed that dietary DOP significantly decreased the feed consumption and feed conversion ratio of layers (p < 0.05) without having any significant effects on egg production, egg weight and egg mass. None of the exterior egg quality parameters were significantly affected by the dietary supplementation of DOP (p > 0.05). Among interior egg quality attributes, the albumen height, albumen index, yolk color, and Haugh unit were all considerably elevated through supplementation of 10% DOP (p < 0.05). Nevertheless, the yolk index was raised by both 5% and 10% DOP supplementation (p < 0.05). The relative weight of ovarian grape and oviduct did not affect by the supplementation of DOP with layer diet (p > 0.05). In summary, it may be said that layer diets can be supplemented with DOP up to 10% level to improve FCR, albumen index, yolk index, yolk color and Haugh unit without compromising egg production or exterior egg quality. Further studies are recommended with layer diets supplemented with DOP at levels higher than 10% to determine the ideal DOP dose during other production periods in various layer strains. Bangladesh Journal of Animal Science 51 (3): 98-106, 2022